The Legal Framework regulating the High Commission for Digitization - BOUAOUNE, Zakarya (Journal of Human Sciences, 2025)
The shift towards a digital community requires enormous mechanisms and human and material resources. The High Commission for Digitalization is designated as the principal authority overseeing this endeavor, assuming a pivotal and active role in the realization of the objectives established by the national digitalization strategy. The legislator has endowed the Commission with a range of competencies aimed at promoting the utilization of modern technology and advancing internet development in accordance with the aspirations of public authorities.